Governance Transformation: Analysis of the Effectiveness of Good University Governance in Higher Education - Rukmana, Novayanti Sopia; Majid, Ahmad Fudhail; Bahri, Syamsul; Hanafi, Nurkharsya Khaer (Jurnal Ilmiah Ilmu Administrasi Publik, 2024)
This study aims to analyze the implementation of Good University Governance (GUG) in Indonesian higher education institutions through a systematic review of existing literature. The method employed is a systematic literature review of 50 scientific articles published between 2015-2024, focusing on GUG implementation in the context of Indonesian higher education. The research identifies five main themes: (1) challenges in GUG implementation, including resistance to change and resource limitations; (2) effective strategies in GUG application, such as continuous training and development of integrated information systems; (3) positive impacts of GUG on institutional performance, particularly in aspects of accreditation and research productivity; (4) the crucial role of leadership in successful GUG implementation; and (5) the significant influence of organizational culture on GUG effectiveness. The study concludes that GUG implementation in Indonesian higher education institutions is a multidimensional process involving structural, cultural, and leadership aspects. Despite facing various challenges, effective GUG implementation has the potential to bring substantial positive impacts on the performance and quality of higher education institutions. These findings emphasize the importance of a holistic and contextual approach in GUG implementation, taking into account the uniqueness of each institution and the Indonesian higher education environment.